2023
DOI: 10.1088/1402-4896/ace707
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of inter-pore spacing of lotus-type pores

Abstract: The present study is to scale the inter-pore spacing and bubble radius required for controlling the porosity of the lotus-type pores in the solid during a unidirectional solidification. The porosity in solid degrade properties of material in welding, casting and additive manufacturing, etc. On the other hand, the ordered cylindrical pores in the material are often used to improve the functional properties, such as the tensile and compression stresses, the impact and acoustic energy absorption, the permeability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The key assumptions underlying this phenomenon are that lotus pores with a spherical cap emerge from distributed spherical bubbles within a static liquid and grow symmetrically along their axis. The interpore spacing w is a consequence of morphological instability [18]. Furthermore, the pores exclusively contain solute gas, with any vaporized gas from the solvent being negligible.…”
Section: Governing Equationsmentioning
confidence: 99%
“…The key assumptions underlying this phenomenon are that lotus pores with a spherical cap emerge from distributed spherical bubbles within a static liquid and grow symmetrically along their axis. The interpore spacing w is a consequence of morphological instability [18]. Furthermore, the pores exclusively contain solute gas, with any vaporized gas from the solvent being negligible.…”
Section: Governing Equationsmentioning
confidence: 99%
“…Based on the analytical solute concentration in liquids and the minimum undercooling criterion provided by the Jackson–Hunt model during eutectic solidification, Liu et al [ 10 ] predicted and experimentally confirmed decreases in porosity, pore radius, and inter-pore spacing as solidification speed, total gas pressure, and partial pressure of hydrogen and argon increased during the gasarite solidification of copper. The Jackson–Hunt theory and analytical solutions of solute concentration were, however, criticized by Lee et al [ 11 ], Drenchev et al [ 12 ], and Wei et al [ 13 ]. Lu et al [ 14 ] also provided a simple thermodynamic model to describe the relationship between processing variables and the pore structure for the ordered porosity copper fabricated via directional solidification.…”
Section: Introductionmentioning
confidence: 99%